Reply to Peluso et al - Seeßle, Jessica; Naujokat, Cord; Oberacker, Phil; Peters, Wolf-Henning; Waterboer, Tim; Müller, Barbara; Merle, Uta (Clinical infectious diseases, 2022)
To date, data on autoantibodies in patients post-COVID-19 are rare. Bhadelia et al [16] detected higher autoantibodies in their post-COVID-19 cohort when compared with controls. However, it has to be considered that the cohort of post-COVID-19 patients was very small (n = 9) and the samples were obtained 1.8 to 7.3 months after acute infection. ANA titers have not been analyzed. Wallukat et al [17] revealed in 31 patients that long-COVID symptoms are associated with the detection of autoantibodies against G-protein-coupled receptors (GPCR) functionally active autoantibodies, which are supposed to play a role in the development of neurological and cardiovascular symptoms. In our recent publication, the proportion of patients having an ANA titer ≥1:160 at 5 and 12 months after acute infection was 40.6% and 43.6% of analyzed patients, respectively.
Gesehen am 10.11.2022
Published: 07 October 2021